Interleukin-7 enhances in vitro development and blastocyst quality in porcine parthenogenetic embryos - Oh, Dongjin; Choi, Hyerin; Kim, Mirae; Cai, Lian; Lee, Joohyeong; Jawad, Ali; Kim, Sohee; Zheng, Haomiao; Lee, Gabsang; Jeon, Yubyeol; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2022)
Interleukin-7 (IL-7), a vital factor that affects cell development, proliferation, and survival, plays an important role in oocyte maturation. However, its role in embryonic development remains unknown. Therefore, in this study, we aimed to investigate the effects of IL-7 supplementation on in vitro culture (IVC) of porcine embryos after parthenogenetic activation (PA) based on characteristics such as cleavage, blastocyst formation rate, intracellular glutathione (GSH) and reactive oxygen species (ROS) levels in cleaved embryos, total cell number, apoptosis rate, and cell lineage specification in blastocysts. Immunofluorescence revealed that IL-7 and its receptor, IL-7Rα (IL-7R) localized in the cytoplasm of porcine parthenote embryos. By supplementing the IVC medium (PZM5) with various concentrations of IL-7, an optimal concentration that enhanced embryonic development, promoted intracellular GSH, and decreased ROS levels in the cleavage stage during porcine embryo IVC was determined. Investigation of mRNA expression patterns via qRT-PCR suggested that IL-7 possibly regulated maternal mRNA clearance and zygotic genome activation. Furthermore, IL-7 supplementation reduced blastocyst apoptosis, enhanced the expression of the inner cell mass marker SOX2, and phosphorylated STAT5 levels in the blastocysts. Moreover, it altered the transcription patterns of genes that regulate apoptosis, IL-7 signaling, and development. Thus, we demonstrated the localization of IL-7 and IL-7R in porcine preimplantation embryos in vitro for the first time. Furthermore, we suggest that IL-7 supplementation can be employed to enhance embryonic development and blastocyst quality based on the activation of the transcripts of genes that are involved in developmental competence and IL-7 signaling during in vitro porcine embryo development following PA.